Prevalence of abnormal spermatozoa in tobacco chewing sub-fertile males - Sunanda, Priyadarsini (Medknow Publications & Media Pvt Ltd, 2014)
AIM: The aim of the following study is to find out the prevalence of abnormal spermatozoa and associated functional parameters in clinical semen samples of sub-fertile males with the tobacco chewing habit. SETTINGS AND DESIGN: Retrospective study was conducted at infertility unit of a tertiary health care center, in a period of 3 years. MATERIALS AND METHOD: Semen of 642 males were analyzed; of them 194 men (30.2%) were tobacco chewers and they were grouped according to their intensity of chewing (<10 and ≥ 10 packets/day). Counts, motility, vitality, and morphology of sperms were analyzed. RESULTS: In tobacco chewers, 66% of subjects were oligozoospermic, 85% asthenozoospermic and 28% teratozoospermic. Sperm counts (odds ratio [OR] =2.2; 95% confidence interval [CI]: 1.5-3.09), motility (OR = 3.2; 95% CI: 2.05-4.9), and normal morphology (OR = 8.4; 95% CI: 4.9-14.6) were significantly affected (P = 0.001) in tobacco chewers than the non-chewing group. Further, in comparison to the intensity of tobacco chewing, patients with the intensive practice of using ≥10 packets/day had a significant effect on sperm morphology (P = 0.003, OR = 2.7; 95% CI = 1.41-5.08) only. Structural defects in head (P = 0.001) and cytoplasmic residues (P = 0.001) were found to be positively correlated with the intensive chewing, but no significant changes were found in anomalies in mid-piece and tail. CONCLUSION: The adverse impact of tobacco chewing on semen parameters was evident even with mild chewers, but with the intensive chewing practice, phenotypes of sperms, mainly defects in the head and cytoplasmic residue were severely affected.